Antiepileptic activity of leaves of Leucas aspera. - Ramalingam Ramani; Bindu Madhavi Boddupalli; Ramya Miryala; Ravinder Nath Anisetti; Nagulu Malothu; Deepthi Balla (International Journal of Phytomedicine, 2014)
Leucas aspera (LA) is a plant that has been used in folk medicine to treat asthma, fever, skin diseases and has several pharmacological activities. The antiepileptic property of LA was not yet been studied. Aim: The present study was aimed to investigate the antiepileptic activity of ethanolic extract obtained from leaves of LA on pentylenetetrazole (PTZ) kindling seizures in mice. Method: The ethanolic extract 200mg/kg and 400mg/kg were evaluated for the antiepileptic activity against PTZ (40mg/kg IP) induced seizure method. Diazepam was used as the standard drug. Antiepileptic activity was evaluated by observing seizure intensity, motor coordination, depression and oxidative stress by malondialdehyde (MDA) content. Results: Treatment with extract was found to be in dose dependant manner with significant prolonged onset time, decreased duration and intensity of seizure when compared with vehicle treated group. Extract has even protected the animal from loss of motor coordination and depression. Conclusion: From the results of present study it can be concluded that, the ethanolic extract of leaves of LA protected the animals from seizure effect induced by PTZ and attenuated the oxidative stress induced by PTZ without producing loss of motor coordination and depression.